Determination of antibiotic consumption index for animal originated foods produced in animal husbandry in Iran, 2010 - Aalipour, Fathollah (BioMed Central, 2014)
The public health concerns over the long-term exposure to antibiotics have risen in different parts of the world. The purpose of this study was to investigate the antibiotic consumption pattern in livestock and poultry and to estimate the quantity of antibiotic active ingredient (mg) consumed per unit weight (Kg) of red meat, milk and egg production in Iran in 2010. A cross-sectional study was designed in charmahal - bakhtiary province-Iran. A questioner has been developed by naming 110 types of antibiotics. Twenty two veterinary clinicians and three livestock pharmaceutical distributor companies were included in the survey to determine the antibiotic prescription and distribution pattern in the farms. Veterinary organization of Iran supplied the information of the total antibiotic consumption in different dosage forms. National and international data on the livestock and poultry production were obtained from the relevant official web sites. Tetracycline class of antibiotics was the most common types of antibacterial prescribed and sold to both livestock and poultry farms. Amino glycoside, penicillin and macrolide in the cattle farms and furofenocole in broiler farms were the second most used groups of antibiotics. The quantity of antibiotic active ingredients consumed per unit weight of animal-originated food products was counted as 107.4 mg/kg for both milk and red meat and 249.5 mg/kg for broiler meat and egg. Totally, it was estimated that 133 mg antibiotic substances was used per kg of milk, meat and egg produced in 2010. In comparison to available data for other countries, consumption of antibiotics in livestock and poultry in Iran is higher than developed countries with an exception of South Korea. The findings of the present study could be alarming for the legislative authorities in food security and safety. More clear evaluation should be carried out as well as implementation of national monitoring and inspective programs in order to reach an added safety regarding animal-originated foods.